Prehospital analgesia in children suffering traumatic injury - Durnin, Sheena (My University, 2012)
Pain causes distress and can negatively impact a child’s experience of the hospital environment. It is best practice for pain relief to be administered as soon as possible to reduce stress, anxiety and discomfort. Research has shown that children are at the highest risk of receiving inadequate analgesia.1 Reasons include difficulty in recognising pain, fear of the side effects of analgesia and reservations about masking symptoms
Irish Association for Emergency Medicine
PUBLISHED
Kildare
Keywords: Immunology, Inflammation & Infection; Neuroscience; PAEDIATRIC; PAIN RELIEF; Pain measurement, pain relief, pain recovery; emergency medicine; pain management, pain measurement, pain relief, pain recover